Phylogenetic congruence of ribosomal operon and plastid gene sequences for the Characeae with an emphasis on Tolypella (Characeae, Charophyceae). Issue 2 (1st March 2017) - Pérez, William; Casanova, Michele T.; Hall, John D.; McCourt, Richard M.; Karol, Kenneth G.
Abstract: To clarify species diversity of Tolypella (Characeae, Charophyceae) and the relationship between Tolypella and other genera in Characeae, sequence data from the nuclear ribosomal operon were assembled for 18 individuals of Tolypella . These represented nine named species and two potentially new species from Australia, as well as 13 other taxa of Characeae. Phylogenetic analyses were performed on ribosomal gene sequences (18S, 5.8S and 28S) for Characeae and on ribosomal gene and internal transcribed spacer (ITS) sequences (ribosomal genes + ITS1 + ITS2) for Tolypella . Analyses were also performed on the ribosomal gene and ITS sequences combined with plastid gene sequences ( atp B, psb C and rbc L). Ribosomal gene sequences alone were conservative and their phylogenetic analyses resulted in topologies similar to a previously published plastid gene-based study but with less support and resolution. In contrast, ITS sequences showed greater variability and their addition resulted in greater resolution among some species relationships of Tolypella . The addition of plastid sequences also resulted in greater support and increased resolution in some lineages but not all.